Clinical Questions Construction in Clinical Practice Guidelines: Based on Case-guided Approach - GAO Yicheng; YU Zijin; WANG Yaqi; FANG Rui; WANG Cheng; LI Yuanyuan; DENG Yingjie; BAI Xue; XIANG Wenyuan; FEI Yutong (Xiehe Yixue Zazhi)
Currently, there are practical and technical difficulties in the construction of clinical questions in the development of clinical practice guidelines. Clinicians or guideline developers seldom construct clinical questions based the actual case scenario, leading to some information loss between structured and actual clinical connotation. To overcome this challenge, we proposed a case-guided questions construction approach, and carried out case research and verification in the formulation of the guideline. We found that this method could more efficiently and scientifically assist the formulation of clinical questions, and provide reference for clinicians or guideline developers.